Sosialisasi Pemanfaatan Pantun dalam Upaya Pembentukan Karakter Siswa Kelas V SD Negeri Binaan Khusus Dumai Timur - Sri Rahayu; Indah Widiati; Hermaliza Hermaliza (UIR Press, 2022)
The problem raised in this community service is the use of rhymes in Efforts to Build the Character of Class V Students at the Special Assisted State Elementary School of Dumai Timur. The decline in character / morals that occurs among students / students so that teachers are expected to be able to improve the character of these students through learning rhymes. The purpose of this community service is to provide socialization about the use of rhymes in an effort to build the character of the fifth graders of the Special Guidance Elementary School in East Dumai. It is hoped that after this socialization the character / morals of students will increase in a better direction because literature, especially rhymes, has a very important role in character building efforts, because basically literary works contain many life values ​​that are full of educational values. character in it. The results achieved in this community service activity are an increase in the character/morality of the fifth grade students of SD Negeri Special Guidance for East Dumai which can be seen from the following indicators, namely the increase in positive characters that occur in students, reduced immoral relationships/brawls that occur among students/ students, creating a comfortable learning atmosphere at school.